The Influence of Psychological Conditions on the Level of Confidence of Indoor Hockey Referees in Facing the XXI PON Aceh–North Sumatra 2024 - Mochamad Egi Margiyan; Muhamad Suma Wijaya (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the influence of psychological conditions on the level of self-confidence of indoor hockey referees in facing the XXI PON in Aceh–North Sumatra 2024. A total of 16 nationally licensed referees, who were officially appointed to officiate matches, were sampled in this study using a total sampling technique. The self-confidence measurement instrument refers to the dimensions developed by Vealey, including aspects of mastery, social support, physical/mental readiness, and situational comfort. The research method uses a quantitative approach. Data analysis was carried out through validity and reliability tests, prerequisite tests (normality and linearity), and simple linear regression tests. The results showed that psychological conditions significantly influenced referee self-confidence, with a significance value of 0.014 and an R Square value of 0.363. This means that 36.3% of the variation in referee self-confidence can be explained by psychological conditions experienced. This finding emphasizes the importance of mental readiness in supporting referee performance, especially in high-intensity matches such as PON. Therefore, technical training for referees needs to be balanced with psychological development to increase emotional stability and self-efficacy in decision-making on the field.